Proceedings of the 24th European MPI Users' Group Meeting 2017
DOI: 10.1145/3127024.3127038
|View full text |Cite
|
Sign up to set email alerts
|

Improving the memory access locality of hybrid MPI applications

Abstract: Maintaining memory access locality is continuing to be a challenge for parallel applications and their runtime environments. By exploiting locality, application performance, resource usage, and performance portability can be improved. The main challenge is to detect and fix memory locality issues for applications that use shared-memory programming models for intra-node parallelization. In this paper, we investigate improving memory access locality of a hybrid MPI+OpenMP application in two different ways, by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…In both solutions, scaling was much better than executing the pure MPI‐based implementation. With this experiment, Diener et al observed the influence of memory locality on load balance, A better locality of reference leads to lower stall time due to memory access, resulting in reasonable use of the resources. The same authors reported that AMPI leads to similar locality gains, achieving better performance and scalability than the simplistic hybrid MPI/OpenMP and pure MPI‐based implementations.…”
Section: Related Workmentioning
confidence: 83%
See 3 more Smart Citations
“…In both solutions, scaling was much better than executing the pure MPI‐based implementation. With this experiment, Diener et al observed the influence of memory locality on load balance, A better locality of reference leads to lower stall time due to memory access, resulting in reasonable use of the resources. The same authors reported that AMPI leads to similar locality gains, achieving better performance and scalability than the simplistic hybrid MPI/OpenMP and pure MPI‐based implementations.…”
Section: Related Workmentioning
confidence: 83%
“…For a similar purpose as other investigations, this study analyzed hybrid configurations to evaluate the impact of message passing operations for a large number of processes. Similar to investigations conducted in previous publications, this study evaluated the performance of a hybrid MPI/OpenMP approach concerning load‐balancing and synchronization techniques.…”
Section: Related Workmentioning
confidence: 93%
See 2 more Smart Citations
“…Trabalhos com objetivos parecidos já foram desenvolvidos para outras aplicações, como [Diener et al 2017] em um estudo para aperfeiçoar o acessoà memória em aplicações híbridas MPI/OpenMP e compará-lo com as versões padrão e puramente MPI, e [Bassi et al 2016] que apresenta um modelo de paralelização híbrido MPI/OpenMP para o método Galerkin Descontínuo. Os dois trabalhos desenvolvem a otimização MPI/OpenMP também em arquitetura com memória compartilhada.…”
Section: Trabalhos Relacionadosunclassified